Palliative care for people living with heart failure: European Association for Palliative Care Task Force expert position statement. Issue 1 (29th August 2019) - Sobanski, Piotr Z; Alt-Epping, Bernd; Currow, David C; Goodlin, Sarah J; Grodzicki, Tomasz; Hogg, Karen; Janssen, Daisy J A; Johnson, Miriam J; Krajnik, Małgorzata; Leget, Carlo; Martínez-Sellés, Manuel; Moroni, Matteo; et al.
Abstract: Contrary to common perception, modern palliative care (PC) is applicable to all people with an incurable disease, not only cancer. PC is appropriate at every stage of disease progression, when PC needs emerge. These needs can be of physical, emotional, social, or spiritual nature. This document encourages the use of validated assessment tools to recognize such needs and ascertain efficacy of management. PC interventions should be provided alongside cardiologic management. Treating breathlessness is more effective, when cardiologic management is supported by PC interventions. Treating other symptoms like pain or depression requires predominantly PC interventions. Advance Care Planning aims to ensure that the future treatment and care the person receives is concordant with their personal values and goals, even after losing decision-making capacity. It should include also disease specific aspects, such as modification of implantable device activity at the end of life. The Whole Person Care concept describes the inseparability of the physical, emotional, and spiritual dimensions of the human being. Addressing psychological and spiritual needs, together with medical treatment, maintains personal integrity and promotes emotional healing. Most PC concerns can be addressed by the usual care team, supported by a PC specialist if needed. During dying, the persons' needs may change dynamically and intensive PC is often required. Following the death of a person, bereavement services benefit loved ones. The authors conclude that the inclusion of PC within the regular clinical framework for people with heart failure results in a substantial improvement in quality of life as well as comfort and dignity whilst dying.